Traditional Worldviews of the Slavs and the Balts: Towards Cognitive Comparative Research - Niebrzegowska-Bartmińska, Stanisława (Vilnius University Open Series, 2021)
Since the 1980s, research on linguistic worldview and collective identity, practised by anthropological, cultural, and cognitive linguists, has focused on identifying and defining the basic values of European culture against a possibly broad comparative background. If standard languages and national traditions have been under scrutiny in the project EUROJOS since 2009 (see the partial results in the five volumes of the “Axiological Lexicon of Slavs and Their Neighbours” and several other publications), value systems of folk cultures have not been studied systematically so far. I therefore propose to revive the idea of an ETNOEUROJOS project, parallel to EUROJOS. In an article published in 2013 in the journal Etnolingwistyka, I postulated that values in folk languages and cultures be investigated within the methodology of the Lublin-based “Dictionary of Folk Stereotypes and Symbols”, whose aim is to reconstruct the folk Polish view of the world and of humans. I now propose, by analogy to the project EUROJOS, to extend the scope of this new program onto the Baltic peoples. A survey conducted among distinguished researchers of Slavic and Baltic traditions has revealed a set of values important for the Slavs (life and health, fam ily and kinship, home, lan d, work and diligence, love, beauty, happiness, wisdom, can didness, honesty, faithfulness, justice, freedom, honour, faith/religion, and God) and for the Balts (lan d, bread, work, fam ily, home). The first stage of the project will be designed to reconstruct the four values common to both the Slavs and the Balts (lan d, work, fam ily, home), to propose parallel descriptions of these values, and to compare these cultural concepts for their semantic invariants. The descriptions obtained in the two projects, EUROJOS and ETNOEUROJOS, will help corroborate or refute the prevalent view that at the level of folk cultures, Slavic and Baltic communities are much closer than at the level of national, elite-shaped cultures.
Keywords: ethnolinguistics; values; linguistic worldview; folk language; folk culture